(untitled) (Research, Society and Development, 2021)
The article portrays the reflections on the experience lived during the continuing education of teachers of the initial years of the municipal network of Cuiabá, in the period of social isolation, due to the pandemic of Covid19. It aims to socialize the training process in the virtual environment, with an emphasis on the contributions of this new normal to the development of the mathematics teaching and learning process. The methodology with a qualitative approach focuses as an investigation in a continuous, systematic and empirical way, grounded with the purpose of improving the teaching practice. The report shows the training developed by teachers who teach mathematics classes in the municipal system in the 4th year of elementary school, conceiving them as subjects of the training process, who had to adapt and reinvent themselves in the classroom in remote education. Given the study carried out, it can be inferred that the challenges experienced by teachers in this atypical scenario are more related to the difficulties in the use of new technologies, as well as the need to translate theory into practice, as it is noted that the theoretical speeches are advanced, when it comes to the construction of a critical view of education and the reality of teaching, however, what is observed are practices that are still ingrained and crystallized, considered traditional, based on the transmission of knowledge and, consequently, the difficulty of working with digital tools.